Countercyclical Capital Buffer and Monetary Policy - Yoo, Byoung Hark; Jo, Kyoo-Hwan (KDI Journal of Economic Policy, 2012)
This paper explores the effect of the countercyclical capital buffer using a DSGE (Dynamic Stochastic General Equilibrium) model with a banking sector. The main results are following. First, if the CAR (capital asset ratio) rises by 1%p as the countercyclical capital buffer, output and credit would increase less than otherwise by 0.8%p and 1.2%p, respectively. Second, the countercyclical capital buffer would decrease both credit and debt of banks, or deposit, and, as a result, boost the CAR. However, if we are going to use monetary policy to control credit expansion by allowing the interest rate to respond to credit, bank capital would also diminish, which would cause the CAR to be lower.